2022
DOI: 10.1186/s12967-022-03332-8
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric study of variation in kinin peptide profiles in nasal fluids and plasma of adult healthy individuals

Abstract: Background The kallikrein-kinin system is assumed to have a multifunctional role in health and disease, but its in vivo role in humans currently remains unclear owing to the divergence of plasma kinin level data published ranging from the low picomolar to high nanomolar range, even in healthy volunteers. Moreover, existing data are often restricted on reporting levels of single kinins, thus neglecting the distinct effects of active kinins on bradykinin (BK) receptors considering diverse metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Gangnus et al (2022) recently reported NLF kinin peptide quantification using a fully validated LC-MS/MS method employing solid-phase extraction with urea normalization. 43 The assay achieved high sensitivity with reported LLOQ for kinin peptide quantification in NLF of 1.9 pmol/L. Therefore, the approach reported herein is the first description of quantitative biotherapeutic bioanalysis in NLF using a hybrid LBA-LC-MS/MS method with concentration normalization via urea correlation (described elsewhere).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gangnus et al (2022) recently reported NLF kinin peptide quantification using a fully validated LC-MS/MS method employing solid-phase extraction with urea normalization. 43 The assay achieved high sensitivity with reported LLOQ for kinin peptide quantification in NLF of 1.9 pmol/L. Therefore, the approach reported herein is the first description of quantitative biotherapeutic bioanalysis in NLF using a hybrid LBA-LC-MS/MS method with concentration normalization via urea correlation (described elsewhere).…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, only one LC-MS/MS method related to protein profiling in NLF has been reported in peer-reviewed publications to date. Gangnus et al (2022) recently reported NLF kinin peptide quantification using a fully validated LC-MS/MS method employing solid-phase extraction with urea normalization . The assay achieved high sensitivity with reported LLOQ for kinin peptide quantification in NLF of 1.9 pmol/L.…”
Section: Discussionmentioning
confidence: 99%